A proposta inovadora da escola Projeto Âncora e suas implicações pedagógicas em uma escola convencional - Costa, Vitor Aparecido Pereira da (Universidade Federal de São Carlos, 2019)
This project arose from worries caused by a brazilian Math Education increasingly disappointing in the public Middle Schools and, in this context, it had as objective to contribute with a new didactic view of this area of knowledge, by means of the adaptation of an activity, based on the innovative method of the School Projeto Âncora, in a conventional school in order to answer the following issue of research: Which contributions the use of the Mathematics Didactics of an innovative school can propitiate to the Teaching of Mathematics of a conventional school? In search of an elucidation to this question, it was conducted a field research at Projeto Âncora to explore their Mathematics Didactic. From the collected notes in the visits, it was possible to execute an experimentation with a multi-age group of 10 students (6º to 9º grades) who worked in the building of checkerboards, developing, in a practical way, basic abilities of geometry and arithmetic. The findings of this study showed a satisfying indicative to answer the issue of research, namely, it was possible to notice contributions generated from this adaptive proposal, such as the incentive of an integrated view of Math, the efficacy of a multi-age group and the proactive participation of the students during the whole experimentation, justified the viability of similar didactic adaptations in conventional schools as long as there are structural conditions and support of the school management.
The innovative proposal of the school Projeto Âncora and its pedagogical implications in a conventional school
Keywords: Educação Matemática; Didática da Matemática; Projeto Âncora; Ensino Básico; Math Education; Mathematics Didactics; Middle School; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL